Pelindian Bijih Emas Menggunakan Natrium Tisulfat 1 M dan Hidrogen Peroksida 30% : Pelindian Bijih Emas Menggunakan Natrium Tisulfat 1 M dan Hidrogen Peroksida 30% - syamsul bahtiar (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2024)
One of the minerals that has high economic value, so that this mineral is often exploited on a large scale, especially in West Sumbawa Regency, is the metallic gold mineral (Au). In general, the gold leaching processuses cyanidation and amalgamation methods, but these two methods have a high degree of toxicity to theenvironment. One alternative method of leaching gold ore is using sodium thiosulfate. The use of sodiumthiosulphate is considered very ef ective, due to high gold recovery, low risk to the environment, faster dissolution of gold compared to cyanide and the reagent used is also quite economical. Leaching was carriedout using 200 mesh size of gold ore taken at Pekirum Village with sodium thiosulphate as a reagent andhydrogen peroxide as an oxidizing agent. In this study, the leaching process was carried out using aconcentration of 1 M sodium thiosulphate, 30% H?O? concentration, 6 hours of leaching time and a temperatureof 60°C. The characterization results using AAS showed that the percentage of gold recovery using sodiumthiosulfate and H?O?